sRNA and cis-antisense sRNA identification in Staphylococcus aureus highlights an unusual sRNA gene cluster with one encoding a secreted peptide - Julie Bronsard (Nature Portfolio, 2017)
Abstract The human pathogen Staphylococcus aureus expresses a set of transcriptional factors and small RNAs (sRNAs) to adapt to environmental variations. Recent harmonization of staphylococcal sRNA data allowed us to search for novel sRNAs using DETR’PROK, a computational pipeline for identifying sRNA in prokaryotes. We performed RNA-Seq on Newman strain and identified a set of 48 sRNA candidates. To avoid bioinformatic artefacts, we applied a series of cut-offs and tested experimentally each selected intergenic region. This narrowed the field to 24 expressed sRNAs, of which 21 were new and designated with Srn identifiers. Further examination of these loci revealed that one exhibited an unusual condensed sRNA cluster of about 650 nucleotides. We determined the transcriptional start sites within this region and demonstrated the presence of three contiguous sRNA genes (srn_9342, srn_9344 and srn_9345) expressed from the positive strand, and two others (srn_9343 and srn_9346) transcribed from the opposite one. Using comparative genomics, we showed that genetic organization of the srn_9342-9346 locus is specific to Newman and that its expression is growth-phase dependent and subjected to nutrient deprivation and oxidative stress. Finally, we demonstrated that srn_9343 encodes a secreted peptide that could belong to a novel S. aureus toxin-antitoxin system.